2020
DOI: 10.1371/journal.pbio.3000606
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-wide identification of HSP70/HSC70 chaperone clients in human cells

Abstract: The 70 kDa heat shock protein (HSP70) family of chaperones are the front line of protection from stress-induced misfolding and aggregation of polypeptides in most organisms and are responsible for promoting the stability, folding, and degradation of clients to maintain cellular protein homeostasis. Here, we demonstrate quantitative identification of HSP70 and 71 kDa heat shock cognate (HSC70) clients using a ubiquitin-mediated proximity tagging strategy and show that, despite their high degree of similarity, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 89 publications
3
42
0
3
Order By: Relevance
“…In addition to interacting with co-chaperones, Hsp70 and Hsc70 exhibited a preference for newly translated proteins and ‘orphan’ proteins, which are monomeric proteins that require binding to other proteins for stability and function. Such a preference confirmed that the Hsp70 family plays an essential role in nascent polypeptide folding and protein complex formation ( Ryu et al, 2020 ). Intriguingly, expression of a misfolded protein such as ALS-linked SOD1 shifted the interactome for Hsp70 and Hsc70, with Hsc70 showing more significant engagement with disordered proteins upon SOD1 expression ( Ryu et al, 2020 ).…”
Section: Hsp110 Hsp70 and Hsp40supporting
confidence: 56%
See 2 more Smart Citations
“…In addition to interacting with co-chaperones, Hsp70 and Hsc70 exhibited a preference for newly translated proteins and ‘orphan’ proteins, which are monomeric proteins that require binding to other proteins for stability and function. Such a preference confirmed that the Hsp70 family plays an essential role in nascent polypeptide folding and protein complex formation ( Ryu et al, 2020 ). Intriguingly, expression of a misfolded protein such as ALS-linked SOD1 shifted the interactome for Hsp70 and Hsc70, with Hsc70 showing more significant engagement with disordered proteins upon SOD1 expression ( Ryu et al, 2020 ).…”
Section: Hsp110 Hsp70 and Hsp40supporting
confidence: 56%
“…Such a preference confirmed that the Hsp70 family plays an essential role in nascent polypeptide folding and protein complex formation ( Ryu et al, 2020 ). Intriguingly, expression of a misfolded protein such as ALS-linked SOD1 shifted the interactome for Hsp70 and Hsc70, with Hsc70 showing more significant engagement with disordered proteins upon SOD1 expression ( Ryu et al, 2020 ). Thus, Hsp70 and Hsc70 are general folding chaperones and also function as part of a disaggregase system to reverse protein aggregation.…”
Section: Hsp110 Hsp70 and Hsp40supporting
confidence: 56%
See 1 more Smart Citation
“…In general HSP70-type chaperones have a similar structure and allosteric cycle, and thus show wide functional redundancy [87]. In contrast, a recent proteome-wide study by Ryu, et al shows that there is essentially no substrate specificity overlap between the HSP70 and HSC70 families, except that they share newly synthesized proteins as common substrates [88].…”
Section: Hsp70-type Chaperonesmentioning
confidence: 99%
“…HSP70s (HSPAs) are among the most ubiquitous chaperones, and they have been shown to play a key role in maintaining protein homeostasis in virtually all domains of life (Gupta and Singh 1994; Hunt and Morimoto 1985; Lindquist and Craig 1988). Upon cross-referencing the NIA and aggregating fractions against a recently generated client database of HSPA8 (HSC70; constitutively active form of HSP70) and HSPA1A (constitutively active and stress-inducible HSP70) (Ryu et al 2020), we find that HSPA8 and HSPA1A clients are enriched among aggregating proteins (Figure 5C). We also mined the BioGRID human protein-protein interaction database using the complete KEGG dataset of (co)chaperones (168 entries).…”
Section: Resultsmentioning
confidence: 99%